A Study of the Renewal Cycle of Hotel Building Elements in Malaysia - Wei, Zhen; Tabassi, Amin Akhavan (EDP Sciences, 2014)
Penang is the main tourism island which appeals an increasing number of travellers each year. Therefore, the hotels in Penang play a crucial role in the field of Penang tourism. However, recently some problems with the Penang hotels have been brought to light frequently by travellers including domestic and foreign tourists. The reason for this may be due to irregular maintenance as well as the fact that the renewal of the building elements may not have been duly carried out. In light of that, this research investigated the condition of the maintenance and renewal cycle of the building elements of the hotels in Penang. This study was conducted with a quantitative method, using a questionnaire to collect information regarding the condition of maintenance, evaluation of the condition of the building elements and the frequency of building elements renewal. The results revealed that each building element renewal cycle is differing according to the effects of maintenance and its lifespan. In terms of comparison with the renewals in Singapore hotels, there are shortcomings involved in the schedule of element renewals carried out in Penang.